Pelvic organ prolapse: current understanding of the problem - L. V. Tkachenko; N. I. Sviridova; I. A. Gritsenko; V. A. Dolgova; K. Yu. Tikhaeva (Акушерство, гинекология и репродукция)
Pelvic organ prolapse (POP) is a fairly common gynecological problem. The relevance for studying this disease is accounted for by a substantial impact it has on patients' quality of life. A part from physical discomfort, a woman suffering from POP experiences profound emotional depression, a sense of shame, which may result in refusing professional medical care. In the treatment of POP, it is necessary to take into account the features of morphological disorders as well as associated changes in vaginal microbiota. Here, we analyze current insights into POP causes and risk factors. The main advantages and drawbacks for diagnostic methods used have been identified, and promising options for POP predictive assessment are described. The effectiveness of the most common methods for conservative treatment is evaluated. In addition, we also describe the types of contemporary surgical correction as well as new modifications of operations to remove POP.